#### Answer

$$ y'= -6x^{-\frac{5}{2}}.$$

#### Work Step by Step

Recall that $(x^n)'=nx^{n-1}$
Since $ y=4x^{-3/2}$, then the derivative $ y'$ is given by
$$ y'=4(-3/2)x^{-(3/2)-1}=-6x^{-\frac{5}{2}}.$$

Chegg costs money, GradeSaver solutions are free!

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$$ y'= -6x^{-\frac{5}{2}}.$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.